Hypoxanthine Derivatives in Experimental Infections - Claudio De Simone; Edoardo Arrigoni Martelli; Pietro Foresta; Giuseppe Famularo; Roberto Giacomelli; Emilio Jirillo; Vito Ruggiero; Giorgio Tonietti (Canadian Journal of Infectious Diseases)
In vivo treatment with parenterally administered hypoxanthine derivatives, notably ST 789, was able to protect cyclophosphamide-immunosuppressed mice against experimental infections with both bacterial and fungal pathogens. However, the mechanisms accounting for these effects of hypoxanthine derivatives remain to be fully established. In fact, only the treatment with ST 789 resulted in a clear enhancement of the primary antibody production as well as macrophage phagocytic activity, whereas T lymphocyte responsiveness to mitogens and both macrophage- and natural killer-dependent cytotoxicity were not significantly affected. These data, together with the recently shown ability of ST 789 to increase interleukin-6 production, suggest that monocyte/macrophages are likely to be the main cellular target of the immunomodulating activity of ST 789. Finally, in the presentln vivo study, hypoxanthine derivatives did not enhance the mean survival time of tumour-bearing immunosuppressed mice.